WAYS TO WRITE CODE ON ANDROID DEVICES (American Journal of Technology and Applied Sciences, 2023)
In today’s digital age, smartphones and tablets have become powerful tools for various tasks, including programming. Android devices, with their versatility and accessibility, can be excellent platforms for coding on the go. Whether you’re an experienced developer or just getting started, there are several ways to write code on Android devices. In this article, we’ll explore different methods and tools that allow you to harness the potential of your Android device for coding.